4D Bioprinting for Biomedical Applications. Issue 9 (September 2016) - Gao, Bin; Yang, Qingzhen; Zhao, Xin; Jin, Guorui; Ma, Yufei; Xu, Feng
Abstract : 3D bioprinting has been developed to effectively and rapidly pattern living cells and biomaterials, aiming to create complex bioconstructs. However, placing biocompatible materials or cells into direct contact via bioprinting is necessary but insufficient for creating these constructs. Therefore, '4D bioprinting' has emerged recently, where 'time' is integrated with 3D bioprinting as the fourth dimension, and the printed objects can change their shapes or functionalities when an external stimulus is imposed or when cell fusion or postprinting self-assembly occurs. In this review, we highlight recent developments in 4D bioprinting technology. Additionally, we review the uses of 4D bioprinting in tissue engineering and drug delivery. Finally, we discuss the major roadblocks to this approach, together with possible solutions, to provide future perspectives on this technology. Trends: 3D bioprinting has found widespread application in various engineering and biomedical fields; however, 3D bioprinting is static and inanimate because it considers only the initial state of the printed object. Recently, 'time' has been integrated with 3D bioprinting as the fourth dimension, so-called '4D bioprinting', where printed objects (e.g., biocompatible responsive materials or cells) are capable of changing their shapes or functionalities with time when an external stimulus is imposed. This advance in printing responsive materials that can change their shape, or materials that can reorganize with cellular self-organization, has broadened the applications of 4D bioprinting in various biomedical fields, such as tissue engineering and drug delivery.